Performance Analysis of 18-Slot 12-Pole Ring-Type Orbital Electric Motor With Variations Of Neodymium and Low-Carbon Steel Rotors Using Femm 4.2 Software - Aryadi, Widya; Putra Julian Valentino, Michael; Apriaskar, Esa (Rekayasa, 2025)
This study aims to evaluate the performance of a ring-type orbital electric motor by examining the effects of variations in magnet position and configuration on flux linkage, force, and torque, and by comparing the results with those of a radial electric motor. The method employed is a 2D numerical simulation using FEMM 4.2 software. The design variations include the use of 0% (Pure) permanent magnets as well as magnets with lamination levels of 25%, 35%, and 50% for the orbital motor type. The simulation results indicate that the orbital motor with 0% (Pure) permanent magnets achieves the highest flux linkage of 3.13 Weber and the highest maximum torque of 336 Nm. For maximum force, the orbital motor with 25% laminated magnets shows the best result at 5207 N. Conversely, the radial motor with 0% (Pure) permanent magnets exhibits the lowest performance across all three parameters. Additionally, increasing the magnet lamination percentage does not always improve performance, as a decline is observed at 50% lamination. Overall, the orbital motor demonstrates superior performance compared to the radial motor.